Пошаговое объяснение:
3/8-(1/9-5/8)=3/8-1/9+5/8=3/8+5/8-1/9=8/8-1/9=1-1/9=9/9-1/9=8/9
8/9
3/8 - ( 1/9 - 5/8) = 3/8 - 1/9 + 5/8 = (3/8 + 5/8) - 1/9 = 1 - 1/9 = 9/9 - 1/9 = 8/9.
1 (если нужно обьяснение) - единицу взяли из 3/8 + 5/8 = 8/8 = 1
Пошаговое объяснение:
3/8-(1/9-5/8)=3/8-1/9+5/8=3/8+5/8-1/9=8/8-1/9=1-1/9=9/9-1/9=8/9
8/9
Пошаговое объяснение:
3/8 - ( 1/9 - 5/8) = 3/8 - 1/9 + 5/8 = (3/8 + 5/8) - 1/9 = 1 - 1/9 = 9/9 - 1/9 = 8/9.
1 (если нужно обьяснение) - единицу взяли из 3/8 + 5/8 = 8/8 = 1